Prevalence and correlates of contraceptive use among adolescent mothers: Results from a cross-sectional survey in Ouagadougou, Burkina Faso, and Blantyre, Malawi - Emmanuel Oloche Otukpa; Alister Munthali; Nathalie Sawadogo; Boniface Ayanbekongshie Ushie; Anthony Idowu Ajayi (PLoS ONE, 2025)
Background Adolescent motherhood remains a pressing public health challenge in sub-Saharan Africa, where repeat pregnancies exacerbate the risks of maternal morbidity, disrupted education, and entrenched economic vulnerability. Contraceptive use among sexually active adolescent mothers offers a critical pathway to mitigate these adverse outcomes, yet empirical evidence on prevalence, determinants, and barriers to contraceptive uptake within this population remains strikingly limited across the region. Our study examines contraceptive use, its correlates, and reasons for non-use of contraception among adolescent mothers (aged 12–19) in Ouagadougou, Burkina Faso and Blantyre, Malawi. Methodology The data analyzed for this study were part of a larger cross-sectional survey on the lived experiences of pregnant and parenting girls. For this study, we limited our analysis to 628 (Ouagadougou) and 500 (Blantyre) adolescent mothers who were neither pregnant nor trying to get pregnant. We randomly selected urban and rural enumeration areas (EAs) in the study settings, conducted household listing, and identified eligible participants whom we interviewed. We used interviewer-administered questionnaires to obtain information on contraceptive awareness, use, and reason for non-use, and analyzed the data using descriptive and inferential statistics. Results Knowledge of contraceptive methods is nearly universal among adolescent mothers, and the contraceptive use prevalence was higher than the national average in both study settings. Single adolescent mothers were significantly less likely to be currently using any contraceptive methods (AOR: 0.75; 95% CI: 0.61–0.93 in Burkina Faso; AOR: 0.60; 95% CI: 0.50–0.71 in Malawi) or any modern methods (AOR: 0.66; 95% CI: 0.49–0.90 in Burkina Faso; AOR: 0.55; 95% CI: 0.46–0.66 in Malawi) compared to their married counterparts in both countries. Adolescent mothers aged 19 were more likely to be current users of any contraceptives compared to those aged 16 or younger in Burkina Faso (AOR: 1.55; 95% CI: 1.07–2.26) and were also more likely to have ever used any methods in Malawi (AOR: 1.28; 95% CI: 1.07–1.53). Infrequent sex (Malawi, 64.9%; Burkina |Faso, 36.6%) was the main reason for contraceptive non-use, though fear of side-effects (17.7%) and religious prohibition (16.6%) also stood out. Conclusion A substantial proportion of adolescent mothers, especially single and younger adolescents, are not using any contraceptive methods or relying on less effective methods. These results underscore the need for more interventions targeting adolescent mothers with accurate information on contraceptive methods. These interventions should address the religious objection to contraceptives in Burkina Faso and infrequent sex in Malawi.